Postpartum-specific vital sign reference ranges - Green, L; Pullon, R; Mackillop, L; Gerry, S; Birks, J; Salvi, D; Davidson, S; Loerup, L; Tarassenko, L; Mossop, J; Edwards, C; Gauntlett, R; et al. (Lippincott, Williams & Wilkins, 2021)
Objective: To estimate normal ranges for postpartum maternal vital signs.